Legislating the Melanesian Way: Bernard Narokobi and the Law Reform Commission of Papua New Guinea. - Golub, Alex (Journal of Pacific History, 2020)
A common criticism of Bernard Narokobi is that his vision of the 'Melanesian Way' was vague and imprecise. This article argues against this claim by describing the activities Narokobi undertook as the head of the Law Reform Commission of Papua New Guinea (1975–8). Using the example of his suggested revision of adultery laws, this article shows that Narokobi realized his abstract vision of the Melanesian Way in the most concrete and specific way possible: by attempting to reform the law. Much of Narokobi's legal reform work was unsuccessful, but a full understanding of his philosophy can only be achieved by reading his legal work alongside his published writings like The Melanesian Way.